Pengaruh Quality of Work Life Terhadap Work Engagrement Pustakawan Pada UPT Perpustakaan Universitas Riau - Thamrin Hasan; Mohamad Djaenudin (Jurnal Gema Pustakawan, 2024)
This study aims to identify the relationship between quality of work life and work engagement among librarians. The research method used is quantitative with a saturated sampling technique, involving 22 librarians who have worked for at least two years. Data were collected using two scales: the quality of work life scale and the work engagement scale. Data analysis was conducted using the product-moment correlation test. The analysis results show a significant relationship between quality of work life and work engagement among librarians, with a significance value of 0.000 (p<0.005) and a correlation coefficient of 0.481. This indicates a positive correlation between the two variables. Higher quality of work life corresponds to higher work engagement among librarians with their library institutions. Conversely, lower quality of work life is associated with lower work engagement. The conclusion of this study is that improving the quality of work life can enhance work engagement among librarians. A good quality of work life creates a supportive and motivating work environment, which in turn increases their engagement with the library institution. On the other hand, poor quality of work life can reduce librarians' motivation and engagement. Therefore, library institutions need to pay attention to and improve the quality of work life to achieve better work engagement. This study provides empirical evidence that quality of work life plays a crucial role in enhancing work engagement among librarians.